The Effect of Organizational Culture on Employee Performance: Job Satisfaction as a Mediating Variable and Transformational Leadership as a Moderating Variable - Ivan Dananjaya; Majang Palupi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of organizational culture on employee performance, with job satisfaction as a mediating variable and transformational leadership as a moderating variable. Organizational culture is considered an important factor in shaping employee attitudes and behavior, which in turn influences job satisfaction and performance. This research applies a quantitative approach using a census sampling technique involving 86 civil servant employees. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0. The results indicate that organizational culture does not have a significant direct effect on employee performance, but has a positive and significant effect on job satisfaction. Furthermore, job satisfaction has a positive and significant effect on employee performance and mediates the relationship between organizational culture and employee performance. However, transformational leadership does not significantly moderate the relationship between organizational culture and job satisfaction. These findings suggest that employee performance is more strongly influenced by psychological factors such as job satisfaction rather than direct organizational cultural practices.